Successful management of fatal peripartum cardiomyopathy in a young pregnant woman: A case report. Issue 15 (April 2018) - Huang, Yaqing; Chen, Tianqi; Zhang, Meiqi; Yang, Xianghong; Ding, Guodong; Yang, Liwei
Abstract: Rationale: Peripartum cardiomyopathy (PPCM) is a rare and life-threatening form of pregnancy associated myocardial disease. Patient concerns: In the present report, we describe a case of a patient with PPCM at 33 weeks of gestation with stillbirth and cardiorespiratory failure. Diagnoses: Peripartum cardiomyopathy. Interventions: The patient underwent emergency cesarean section (CS) and comprehensive medical treatments, including bromocriptine, as well as positive inotropic agents and diuretics after the CS. Outcomes: She had an uneventful recovery period, and was discharged 9 days after surgery. Her heart function was restored within 6 months after CS, and follow-up echocardiographies indicated normal heart function. Lessons: This case highlights that early diagnosis and timely termination of pregnancy are crucial in the management of PPCM.